Design of Pump Installation Process for Automatic Oil Circulation in Generator to Lubricate the Engine - Naufal Aditia Putra; Ayub Wimatra; Heru Kusdarwanto (Sean Institute, 2025)
Genset (generator set) is a device that functions to generate electrical power. Referred to as a generator set with the understanding is a set of combined equipment from two different devices, namely the engine and generator or alternator. The engine as a rotating device while the generator or alternator as a generating device. Genset maintenance must be heated every day with a time range of 10-15 minutes for oil lubrication circulation in all parts of the engine. This is because the generator uses a battery that requires consistent battery charging. Based on the problems above, to carry out fuel efficiency in carrying out generator engine maintenance, a pump installation process design is carried out as an automatic generator oil circulation to lubricate the generator engine.